Posterior mediastinal capillary hemangioma misdiagnosed as neurofibromas: a rare case report and review of the literature - Bijam Zeyaian; Neda Soleimani; Bita Geramizadeh (Rare Tumors, 2015)
Capillary hemangioma is a common benign tumor which can occur everywhere in the whole body, however its occurrence in posterior mediastinum is extremely rare, and to the best of our knowledge less than 20 cases have been reported in the English literature so far. Here in we report a 65-year-old lady who presented with prolonged cough and diagnosed to have a posterior mediastinal mass. Before operation, according to the site of tumor, it has been diagnosed as neurofibroma. It is very important to consider hemangioma before operation to reduce surgical complications, and it should be in the differential diagnosis of posterior mediastinal masses.